A Hybrid Mean Value Involving Dedekind Sums and the Generalized Kloosterman Sums - Xiaowei Pan; Xiaoyan Guo (Journal of Mathematics)
In this paper, we use the mean value theorem of Dirichlet L-functions and the properties of Gauss sums and Dedekind sums to study the hybrid mean value problem involving Dedekind sums and the general Kloosterman sums and give an interesting identity for it.